THE USE OF YOUTUBE VIDEO AS MEDIA IN MULTIGRADE ENGLISH DEPARTMENT STUDENTS TO IMPROVE CONVERSATIONAL COMPETENCE IN SPEAKING CLASS - authar, nailul; Afandi, Mujad Didien; Muflihah, Tatik (Universitas Nahdatul Ulama Surabaya, 2021)
Abstract: Miller (1999:1) defines multigrade class as a class in which students of two or more adjacent grade levels are taught in one classroom by one teacher for most of the day. It is obviously hard to be imagined that a teacher teaches grade one, two, and three concurrently. This study also is highlighted of the using YouTube as a media where students can take any kind of references that can help them to improve their English skill is better. Such as; watching daily vlog from youtuber outside Indonesia, listening while singing English song by watching several lyrics video. weather news report, stand-up comedy, gossip news which telling about the Hollywood celebrity, etc. from those kinds of references that available in YouTube, it is hoped that students also can be more attracted to learn English clearly. Considering those all, teaching multigrade students possibly will not run well unless the students correspondingly add some varieties way to comprehend English easily. It needs something that make students are busy and focus on what will be learned and achieve later. Therefore, watching YouTube video is attempted in this study. This research belonged to qualitative research. The participants of the study in this research are eleven multigrade English students in speaking class who were taught by the researcher. The data of this study was taken from the students’ response. those are taken from the interview of each group through online interview. The study are undertaken for a month while teaching learning activities are committed twice a week, 90 minutes for each meeting. This study brings in a simple finding that the students of multigrade class can be formed well-enough as well as single-grade class, nevertheless it is unavoidable that in the process oftenly faced the obstacle, such as lower grade students who sulking, quarrelling, and lecturer also has to do extra effort to keep the learning process is on the proper track. This is also indicates that using YouTube video as a media is effective to be implemented on multigrade class with limited number of participants because the different result possibly emerges when there are more participants and more various grades of students. It is hoped that there will be another researcher can make further research to get deeper study about the topic in the same field in order to get more enlightenment result about YouTube as a media of learning especially in teaching multigrade English students. Keywords: Speaking class, Multigrade students, YouTube Abstrak: Miller (1999: 1) mendefinisikan kelas multigrade sebagai kelas di mana siswa dari dua atau lebih tingkat kelas yang berdekatan diajarkan di satu kelas oleh satu guru untuk sebagian besar hari. Jelas sulit untuk dibayangkan bahwa seorang guru mengajar kelas satu, dua, dan tiga secara bersamaan. Studi ini juga menyoroti penggunaan Youtube sebagai media di mana siswa dapat mengambil segala jenis referensi yang dapat membantu mereka untuk meningkatkan keterampilan bahasa Inggris mereka lebih baik. Seperti; menonton vlog harian dari youtuber luar Indonesia, mendengarkan sambil menyanyikan lagu berbahasa Inggris dengan menonton beberapa video lirik. Laporan berita cuaca, stand-up comedy, berita gosip yang menceritakan tentang selebriti Hollywood, dll dari referensi semacam itu yang tersedia di YouTube, diharapkan siswa juga dapat lebih tertarik untuk belajar bahasa Inggris dengan jelas. Mengingat semua itu, mengajar siswa multigrade mungkin tidak akan berjalan dengan baik kecuali siswa dengan demikian menambahkan beberapa jenis cara untuk memahami bahasa Inggris dengan mudah. Dibutuhkan sesuatu yang membuat siswa sibuk dan fokus pada apa yang akan dipelajari dan dicapai nanti. Oleh karena itu, menonton video YouTube dicoba dalam penelitian ini. Penelitian ini termasuk dalam penelitian kualitatif. Peserta penelitian dalam penelitian ini adalah sebelas siswa bahasa Inggris multigrade di kelas berbicara yang diajarkan oleh peneliti. Data penelitian ini diambil dari respon siswa. yang diambil dari wawancara masing-masing kelompok melalui wawancara online. Penelitian ini dilakukan selama sebulan sementara kegiatan belajar mengajar dilakukan dua kali seminggu, 90 menit untuk setiap pertemuan. Penelitian ini membawa temuan sederhana bahwa siswa kelas multigrade dapat dibentuk cukup baik serta kelas tunggal, namun tidak dapat dihindari bahwa dalam proses sering menghadapi hambatan, seperti siswa kelas bawah yang merajuk, bertengkar, dan dosen juga harus melakukan upaya ekstra untuk menjaga proses pembelajaran berada di jalur yang benar. Ini juga menunjukkan bahwa menggunakan video YouTube sebagai media efektif untuk diimplementasikan pada kelas multigrade dengan jumlah peserta yang terbatas karena hasil yang berbeda mungkin muncul ketika ada lebih banyak peserta dan lebih banyak nilai siswa yang berbeda. Diharapkan ada peneliti lain yang dapat melakukan penelitian lebih lanjut untuk mendapatkan kajian yang lebih mendalam tentang topik di bidang yang sama guna mendapatkan hasil pencerahan yang lebih banyak tentang YouTube sebagai media pembelajaran khususnya dalam pengajaran bahasa Inggris kelas rangkap. Kata kunci: Kelas berbicara, siswa Multigrade, YouTube